Breast cancer screening among Hispanic and non‐Hispanic White women by birthplace in the Sister Study - Charlotte J. Talham (Cancer Medicine, 2022)
Abstract Background Hispanic/Latina women are less likely to be diagnosed with local stage breast cancer than White women. Additionally, foreign‐born women have lower mammography rates than US‐born women. We evaluated the combined effect of birthplace and race/ethnicity on screening habits of women at higher‐than‐average risk of breast cancer. Methods Multinomial logistic regression was used to evaluate breast cancer screening in 44,524 women in the Sister Study cohort. Screening methods ascertained at enrollment (2003–2009) included mammography, ultrasound, and magnetic resonance imaging. Timing of screening was assessed as recently (≤2 years ago), formerly (>2 years ago), and never screened. Adjustments included sociodemographic, socioeconomic, and health variables. Results Most women in the sample were US‐born non‐Hispanic/Latina White (92%), were ≥50 years old (73%), had one first‐degree female relative with breast cancer (73%), and were screened in the past two years (97%). US‐born Hispanic/Latina women had higher odds (odds ratio [OR] = 1.47, 95% confidence interval [CI] = 1.08–2.00) than US‐born non‐Hispanic/Latina White women of not having received a breast cancer screening in the past 2 years, relative to a recent screening. Similarly, foreign‐born Hispanic/Latina women had higher odds (OR = 1.63, 95% CI = 1.10–2.41) than US‐born non‐Hispanic/Latina White women of never having received a breast cancer screening. Conclusion We observed that Hispanic/Latina women have higher odds of never and dated breast cancer screenings compared to US‐born White women. Birthplace and race/ethnicity each contribute to disparities in who receives preventative health care in the United States. It is critical to include birthplace when evaluating health behaviors in minority groups.